Psychological Well Being of Adolescents Who Experience Catcalling: A Phenomenological Study - Hasgimianti; Raden Deceu Berlian Purnama; Raja Rahima Munawarah Raja Ahmad; Yunita Efendi (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Catcalling is a type of sexual harassment that often occurs in public spaces. The act of catcalling is sometimes seen as usual by society, but it can psychologically impact individuals if they experience catcalling. This research aims to describe the psychological well-being of teenagers who experience catcalling and analyze the factors that influence the psychological well-being of teenagers who experience catcalling. This research uses a qualitative phenomenological approach. The informants are teenagers aged 13-15 years with the criteria of having experienced catcalling and being in the early teenage development stage. There were 15 informants. Data collection techniques used semi-structured interviews. The data analysis technique in this research uses the Colaizi model, where each transcript is identified, checked for accuracy, and analyzed. The results of the study show that teenagers who experience catcalling feel that their psychological well-being is disturbed. In contrast, informants feel that their happiness is disturbed, they have less satisfaction in their lives, tend to experience stress, lack physical and psychological well-being, and experience difficulties maintaining the quality of life with Good. The results of other analyzes also show that the factors that influence the psychological well-being of teenagers who experience catcalling consist of age, gender, religiosity, personality stress, and social support.